DESIGN AND DEVELOPMENT OF MULTIFUNCTIONAL METASURFACE FOR BEAM STEERING AND POLARIZATION CONVERSION - Syed Elliyeen Shah; Muhammad Bilal; Muhammad Usman; Bilal Ur Rehman; Kifayat Ullah; Muhammad Amir; Shahid Bashir; Muhammad Iftikhar (Spectrum of Engineering Sciences, 2025)
This study investigates the design and modelling of a multifunctional metasurface for polarization conversion, optimised with CST Microwave Studio. The metasurface, characterised by a C-shaped unit cell, attains a high polarization conversion efficiency (PCR > 90%) in the C-, X-, Ku-, and K-bands, exhibiting superior performance in the 5.3-5.4 GHz, 7.6-8.5 GHz, and 12.7-14.2 GHz frequency ranges. The research further introduces a broadband reflecting metasurface configuration that exhibits directional scattering characteristics and extensive phase tunability, operating across the 90-300 GHz range. Simulations indicate a phase shift range of +30° to -850 ° and exhibit pronounced directed reflection with reduced side lobes in bistatic radar cross-section (RCS) patterns. These findings highlight the metasurface's applications in advanced communication systems, beamforming, and stealth technologies.